1986
DOI: 10.1139/x86-003
|View full text |Cite
|
Sign up to set email alerts
|

Timing of defoliation and its effect on bud development, starch reserves, and sap sugar concentration in sugar maple

Abstract: Sapling sugar maple (Acersaccharum Marsh.) trees were defoliated artificially at 10-day intervals beginning May 27 and ending August 5, 1981. Refoliation, terminal bud and shoot development, and xylem starch and sap sugar concentration were observed in defoliated and control trees. All defoliated trees refoliated, but decreasingly with later defoliation. Defoliation caused an acceleration in the rate of primordia initiation in terminal shoot apices. After early season defoliations, the developing buds in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…Both NDE and DSI were significantly related to PDEADSM (Table 1); the DSI for the past decade produced the strongest relationships. Studies of defoliation effects on sugar maple have shown that effects on nonstructural carbohydrates, particularly root starch reserves, play a critical role in tree vigor (Parker and Houston 1971;Wargo et al 1972;Wargo 1981aWargo , 1988bWargo , 1988cWargo , 1999Gregory and Wargo 1986;Renaud and Mauffette 1991). These studies show that the number, severity, and timing (both within a growing season and number of consecutive years) of defoliations and the physiological condition of the tree when defoliation occurs contribute to the outcome (Parker 1981).…”
Section: Association Of Stress With Sugar Maple Declinementioning
confidence: 99%
See 1 more Smart Citation
“…Both NDE and DSI were significantly related to PDEADSM (Table 1); the DSI for the past decade produced the strongest relationships. Studies of defoliation effects on sugar maple have shown that effects on nonstructural carbohydrates, particularly root starch reserves, play a critical role in tree vigor (Parker and Houston 1971;Wargo et al 1972;Wargo 1981aWargo , 1988bWargo , 1988cWargo , 1999Gregory and Wargo 1986;Renaud and Mauffette 1991). These studies show that the number, severity, and timing (both within a growing season and number of consecutive years) of defoliations and the physiological condition of the tree when defoliation occurs contribute to the outcome (Parker 1981).…”
Section: Association Of Stress With Sugar Maple Declinementioning
confidence: 99%
“…These studies show that the number, severity, and timing (both within a growing season and number of consecutive years) of defoliations and the physiological condition of the tree when defoliation occurs contribute to the outcome (Parker 1981). Both the number and the severity of defoliations have a strong negative relationship with root starch reserves at the beginning of the dormant season; defoliations that cause refoliation have the greatest effect (Wargo 1981a(Wargo , 1988b(Wargo , 1988cGregory and Wargo 1986). Sugar maple in some of our stands were more resilient than those in others; some stands with NDE ≥ 2 and DSI ≥4 did not have symptoms of decline, while trees with the same number and severity of defoliations in other stands were declining.…”
Section: Association Of Stress With Sugar Maple Declinementioning
confidence: 99%
“…However, they also found that the same trees had elevated levels of fall root sugars (glucose and fructose). Mortality of sugar maple has been associated with shoot and root starch depletion in artificially defoliated trees (Gregory and Wargo 1986). Severe insect defoliation reduced fall root starch levels in sugar maple (Kolb et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Seedling stage was identified to be the most critical stage [12] . Intensive grazing during growth period lowers the re-growth and renewing capacity of the plants [25], which is attributed of the fact that the level of non-structural carbohydrates reserve lowers due to defoliation [26]. Impact of grazing on biodiversity is a complicated and diverse issue that vary spatially and temporally [27] and management effort must be location and time specific.…”
Section: Introductionmentioning
confidence: 99%